Zur vertikalen Differenzierung der Zirkumglobalstrahlung - Havlik, Dieter (ERDKUNDE, 1972)
Vertical differences of circumglobal radiation (2GS), as measured with the spherical pyranometer Bellani, have been analyzed for the stations Basel-Binningen, Höchenschwand, and Weißfluhjoch. For more detailed research, it seemed useful to introduce a new parameter, the average intensity of circumglobal radiation per hour of locally possible sunshine (ZI). Both annual march and frequency distribution of ZI are investigated. In the lowlands (Basel) the mean monthly maxima of both ZGS and ZI are observed in summer. In Höchenschwand (middle elevations) the maximum of ZGS appears in July, that of ZI, however, in March. At the higher elevated station of Weißfluhjoch, maximum values of both ZGS and ZI are registered in April, the minimum of ZGS in December, and of ZI in August. Reasons for the different kinds of annual march in the respective altitudes, and their consequences, are discussed.